Methods of integrated assessment of professionally important socio-psychological characteristics of a specialist in pharmacy as a component of the creation - M. I. Harkusha; O. I. Tykhonov; R. V. Sahaidak-Nikitiuk; N. V. Demchenko; O. S. Shpychak (Zaporozhye State Medical University, 2019)
The article proposes a method for evaluating professionally important socio-psychological characteristics of a pharmacy specialist. To determine the level of development of socio-psychological characteristics, the feasibility of using integrated and integral indicators has been proved. Materials and methods. To achieve the goal set in the study, the following methods were used: the method of generalization, grouping and logical analysis, economic and mathematical methods, namely the taxonomy method, which was used to calculate the complex social and psychological components of the level of development of professionally important characteristics of pharmacy specialists and their integral magnitude. The expert method was used to determine the components that make up the professionally important socio-psychological characteristics of pharmacy specialists. The opinion of the respondents is justified, as evidenced by the concordance coefficient exceeding the established threshold value (0.75) and the Pearson criterion (the calculated value of which is higher than the table value taking into account the number of degrees of freedom). 995 pharmacy specialists from all regions of Ukraine participated in the survey. Testing was used to assess the level of development of professionally important social and psychological characteristics of pharmacy specialists. Results. On the basis of the conducted studies, it was proved that the complex indicator of the level of development of professionally important psychological qualities of a pharmacy specialist should include indicators of his psycho-emotional stability, volitional, moral and intellectual qualities.A comprehensive indicator of the level of development of professionally important social qualities of a pharmacy specialist should include indicators of the level of his personal attitude, attitude towards people and work. The indicators included in the listed qualities were determined using the weighted average rank of each component and the level of development of the corresponding qualities determined on the basis of testing by pharmacy specialists. Then, using the taxonomic method, the integral indicator of the level of development of professionally important socio-psychological characteristics was calculated, depending on the size of which the pharmacists were divided into three groups. And on the basis of the separation of pharmacy specialists, the development of directions for the development or improvement of their professionally important socio-psychological characteristics is carried out.Conclusions. The expediency of using complex and integral indicators for assessing the level of development of professionally important socio-psychological characteristics of pharmacists, calculated using the taxonomic method, has been proved.